Meaning Shifts in the Indonesian Translation of Jenny Han’s To All The Boys I’ve Loved Before - Olfi, Trifosa; Sunardi, F.X. Dono (Universitas Negeri Semarang, 2017)
This study discusses the meaning shifts found in the Indonesian translation of Jenny Han‘s To All the Boys I‟ve Loved Before (2014). Shifts, including meaning shifts, often occur in the process of translation of literary works like novel. There are three types of meaning shifts: from general to specific, from specific to general, and shifts caused by socio-cultural factors. This paper examines the meaning shifts in the translation of To All the Boys I‟ve Loved Before from English to Indonesian. The research questions are: 1) what are the meaning shifts found in the Indonesian translation of To All the Boys I‟ve Loved Before?, and 2) what are the causes of those meaning shifts? By means of purposively sampling and comparing the English and Indonesian versions of the novel, it was found 100 sentences with meaning shifts, 13 sentences of which are of from general to specific type, 11 from specific to general, and 76 caused by sociocultural factors. The meaning shifts from general to specific occur because one word in the SL refers to more than one word in the TL, or because one word describing one particular concept in the SL culture is equivalent to several sub-concepts in the TL culture. The meaning shifts form specific to general occur because some sentences have the words that are the name of things that do not exist or are not originated from Indonesia or English words that have equivalents that are more general in Indonesian. For the last category, the writer identifies five specific factors of the shifts, which are the untranslatable idioms or figurative language, parts of the SL culture that are different from the TL culture, English slang or words that has inappropriate equivalents in Indonesian, the contexts of the sentences, and unspecific reasons.